Aluminum alloy plate belt material for printing plate base that does not require processing, and method for manufacturing the same.
Patent Information
- Application Number
- JP2024172643
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-12-19
- Filing Date
- 2024-10-01
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-10-01
AI Technical Summary
【0040】 以下では、実施例を参照しながら、本願の有益な効果を更に説明する。
Smart Images

Figure 0007943885000002 
Figure 0007943885000003 
Figure 0007943885000004
Abstract
Description
[Technical Field]
[0001] The present invention relates to the technical field of aluminum alloy casting, and more specifically to an aluminum alloy plate belt material for a no-process printing plate base and a method for manufacturing the same. [Background technology]
[0002] Aluminum is used in the manufacture of printing plate bases due to its high strength, good surface treatment properties, and good hydrophilicity, giving the printing plate bases advantages such as good stability, high resolution, and strong print resistance. The printing mechanism involves surface treating an aluminum plate, then applying a layer of photosensitive resin to manufacture the printing plate base, and completing the printing by utilizing the ink-hydrophilic properties of the photosensitive resin layer and the hydrophilic properties of the aluminum base in the textured layer. Compared to conventional CTP and PS plates, the pre-processed printing plate base has a multi-layer textured surface, high resolution, is environmentally friendly, and has a very large potential for development.
[0003] Therefore, the problem of matching the tensile strength and grain performance of aluminum material for the no-process printing plate base, as well as streak and pit defects on the surface of the no-process printing plate base, are always bottleneck issues that limit the batch distribution and application of this product. [Overview of the project]
[0004] The main objective of the present invention is to provide an aluminum alloy plate belt material for a no-process printing plate base and a method for manufacturing the same, in order to solve the problem of difficulty in matching the tensile strength and grain performance of aluminum materials for no-process printing plate bases in the prior art.
[0005] To achieve the above objective, according to a first aspect of the present invention, an aluminum alloy plate belt material for a no-process printing plate base is provided, wherein, by mass percentage, the aluminum alloy plate belt material contains 0.02% to 0.10% Si, 0.10% to 0.35% Fe, <0.05% Cu, <0.02% Mn, 0.17% to 0.35% Mg, <0.02% Zn, and <0.03% Ti, with the remainder being Al and several kinds of unavoidable impurities. The aluminum alloy sheet belt material has a total impurity content of <0.15%, a single impurity content of <0.05%, a tensile strength of 170-210 MPa, an electrolytic sand roughness Ra of 0.45-0.55 μm, an Rz of 3.50-4.60 μm, an electrode potential of -0.7 V to -0.9 V, and a number density of Fe-containing second phases exceeding 5 μm in length in the aluminum alloy sheet belt material is ≤10 particles / mm². 2 Therefore, the area ratio occupied by deformed crystal grains in the aluminum alloy plate belt material is ≥ 90%.
[0006] Furthermore, the aluminum alloy plate belt material has a roughness Ra of 0.2 to 0.3 μm and an Rz of 1.5 to 2.5 μm.
[0007] Furthermore, after anodizing, the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is <0.2 mm, and / or the color difference ΔE on the anodized surface of the aluminum alloy sheet belt material is <0.25, and / or the brightness difference ΔL on the anodized surface of the aluminum alloy sheet belt material is <0.25.
[0008] Furthermore, the yield strength of the aluminum alloy plate belt material is ≥160 MPa, and / or the elongation of the aluminum alloy plate belt material is ≥1%, preferably ≥4%.
[0009] According to another aspect of the present invention, a method for manufacturing the aluminum alloy sheet belt material is provided, the manufacturing method comprising the steps of casting, heat treatment, hot rolling, primary cold rolling, intermediate annealing, and secondary cold rolling, which are performed sequentially, wherein the temperature of the intermediate annealing step is 420 to 440°C and the cooling water temperature of the casting step is 19 to 25°C.
[0010] Furthermore, in the intermediate annealing process described above, the heating rate is 20-30°C / hour, and the holding time is 2-4 hours.
[0011] Furthermore, the settling time after the casting process is 30 to 50 minutes, and / or the temperature during the heat treatment process is 440 to 480°C.
[0012] Furthermore, the starting temperature for the hot rolling process is 420-460°C, and / or the final rolling temperature is 270-310°C.
[0013] Furthermore, the rolling speed in the primary cold rolling process is 300 to 1000 m / min.
[0014] Furthermore, the surface roughness of the rolling rollers in the secondary cold rolling process is 0.3 to 0.4 μm, and / or the cold rolling rate in the secondary cold rolling process is 80 to 90%.
[0015] By applying the technical solution of the present invention, the present invention improves the synergistic effect of each element by controlling the content of each element within the above range. Compared to the prior art, the present invention reduces the content of Cu, Si, and Fe elements and increases the content of Mg element, thereby giving the manufactured aluminum alloy plate belt material for pre-processed printing plate bases the above-mentioned tensile strength, electrolytic sand roughness, electrode potential, and surface quality (specifically, by controlling the number density and size of the Fe-containing second phase of the present invention within the above range, it contributes to reducing the degree of streak defects on the surface of the aluminum alloy plate belt material. The above-mentioned low electrode potential helps to form a multilayer sand texture on the surface of the aluminum alloy plate belt material after electrolytic treatment). Furthermore, this gives the aluminum alloy plate belt material for pre-processed printing plate bases high resistance to softening deformation, high resolution, and print resistance, thus solving the problem of difficulty in matching the tensile strength and sand texture performance of the aluminum alloy plate belt material for pre-processed printing plate bases. [Brief explanation of the drawing]
[0016] The drawings, which constitute part of this application, are used to provide a further understanding of the invention, and the exemplary embodiments and their descriptions are used to interpret the invention and do not constitute an unreasonable limitation to the invention. The drawings are as follows:
[0017] [Figure 1] This diagram shows the precipitation and remelting of the Mg2Si phase before and after intermediate annealing of an aluminum alloy plate belt material for a no-process printing plate base provided by Example 1 of the present application. [Figure 2] This is a distribution diagram of the Fe-containing second phase in an aluminum alloy plate belt material for a no-process printing plate base provided by Example 1 of the present application. [Figure 3] This diagram shows the area ratio of deformed crystalline particles in the aluminum alloy plate belt material for a processing-free printing plate base provided by Example 1 of the present application (lighter colors represent deformed crystalline particles, and darker colors represent recrystallized particles). [Figure 4]This is a surface roughness distribution diagram of the aluminum alloy sheet and strip material for process-free printing plate base provided by Example 1 of the present application before and after graining treatment. [Figure 5] This is a three-dimensional topography diagram of the surface after anodizing treatment of the aluminum alloy sheet and strip material for process-free printing plate base provided by Example 1 of the present application. [Figure 6] This is a diagram of the area ratio occupied by deformed crystal grains of the aluminum alloy sheet and strip material for process-free printing plate base provided by Comparative Example 1 of the present application (light color represents deformed crystal grains, and dark color represents recrystallized grains). [Figure 7] This is a surface roughness distribution diagram of the aluminum alloy sheet and strip material for process-free printing plate base provided by Comparative Example 1 of the present application before and after graining treatment. [Figure 8] This is a distribution diagram of Fe-containing second phases and a partial enlarged view thereof of the aluminum alloy sheet and strip material for process-free printing plate base provided by Comparative Example 2 of the present application. [Figure 9] This is a three-dimensional topography diagram of the surface after anodizing treatment of the aluminum alloy sheet and strip material for process-free printing plate base provided by Comparative Example 2 of the present application. [Mode for Carrying Out the Invention]
[0018] It is noted that where there is no conflict, the examples of the present application and the features in the examples can be combined with each other. Hereinafter, the present invention will be described in detail with reference to the drawings and in conjunction with the examples.
[0019] As analyzed in the background art of the present application, the prior art has the problem that it is difficult to match the tensile strength and graining performance of the aluminum material for process-free printing plate base. To solve the above problem, the present invention provides an aluminum alloy sheet and strip material for process-free printing plate base and a manufacturing method thereof.
[0020] In one typical embodiment of the present application, an aluminum alloy sheet belt material for a no-process printing plate base is provided, which, by mass percentage, contains 0.02% to 0.10% Si, 0.10% to 0.35% Fe, <0.05% Cu, <0.02% Mn, 0.17% to 0.35% Mg, <0.02% Zn, and <0.03% Ti, with the remainder being Al and some kind of unavoidable impurities. The total content of pure materials is <0.15%, the content of a single impurity is <0.05%, provided that the tensile strength of the aluminum alloy sheet belt is 170-210 MPa, the electrolytic sand roughness Ra of the aluminum alloy sheet belt is 0.45-0.55 μm, Rz is 3.50-4.60 μm, the electrode potential of the aluminum alloy sheet belt is -0.7 V to -0.9 V, and the number density of Fe-containing second phase particles longer than 5 μm in the aluminum alloy sheet belt is ≤10 particles / mm². 2 Therefore, the area ratio occupied by deformed crystal grains in the aluminum alloy plate belt material is ≥ 90%.
[0021] The present invention improves the synergistic effect of each element by controlling the content of each element within the above range. Compared to the prior art, this application reduces the content of Cu, Si, and Fe and increases the content of Mg, thereby giving the manufactured aluminum alloy plate belt material for no-process printing plate bases the above-mentioned tensile strength, electrolytic sand roughness, electrode potential, and surface quality (specifically, by controlling the number density and size of the Fe-containing second phase in this application within the above range, it contributes to reducing the degree of streak defects on the surface of the aluminum alloy plate belt material. The above-mentioned low electrode potential helps to form a multilayer sand texture on the surface of the aluminum alloy plate belt material after electrolytic treatment). Furthermore, this gives the aluminum alloy plate belt material for no-process printing plate bases high resistance to softening deformation, high resolution, and print resistance, thus solving the problem of difficulty in matching the tensile strength and sand texture performance of the aluminum alloy plate belt material for no-process printing plate bases.
[0022] In one embodiment of the present invention, the roughness Ra of the aluminum alloy plate belt material is 0.2 to 0.3 μm, and the Rz is 1.5 to 2.5 μm.
[0023] Preferably, controlling the roughness of the aluminum alloy sheet belt material within the above range helps to improve the printing resolution of the aluminum alloy sheet belt material itself, and therefore, even after subsequent sandblasting of the aluminum alloy sheet belt material, it still has excellent resolution and satisfies the technical standards and application requirements for aluminum alloy sheet belt material for non-processing printing plate bases.
[0024] In order to improve the print resistance of the aluminum alloy sheet belt material, in one embodiment of the present invention, after anodizing, the diameter of pit defects on the anodic surface of the aluminum alloy sheet belt material is <0.2 mm, and / or the color difference ΔE on the anodic surface of the aluminum alloy sheet belt material is <0.25, and / or the brightness difference ΔL on the anodic surface of the aluminum alloy sheet belt material is <0.25.
[0025] One of the surface defects in the no-processing printing plate base is pit defects. These pit defects are small in size, randomly distributed, and difficult to identify. While they have little impact on the quality of ordinary printing plate bases, they have a significant impact on the quality of high-resolution no-processing printing plate bases. Researchers speculate that during the electrolytic sanding and anodizing processes, Al3Fe has a higher electrode potential than the aluminum substrate, causing preferential corrosion of the surrounding aluminum substrate, thereby eroding the aluminum alloy plate belt material. As the electrolytic sanding and anodizing reactions proceed, the Al3Fe on the surface dissolves or detaches, forming pit defects on the surface of the no-processing printing plate base. This application reduces the electrode potential of the aluminum alloy plate belt material so that the diameter of the pit defects on the anodized surface of the aluminum alloy plate belt material falls within the above range. Consequently, the degree of pit defects on the anodized surface of the aluminum alloy plate belt material is reduced. Preferably, when the color difference ΔE and brightness difference ΔL are within the above range, it is advantageous to further improve the quality of the anodized surface of the aluminum alloy plate belt material.
[0026] In this application, a confocal microscope is used to detect the three-dimensional shape of the pit defects.
[0027] In one embodiment of the present invention, the yield strength of the aluminum alloy plate belt material is ≥160 MPa, and / or the elongation of the aluminum alloy plate belt material is ≥1%, preferably ≥4%.
[0028] Preferably, controlling the yield strength and elongation of the aluminum alloy sheet belt material within the above range is advantageous in improving the resistance to softening deformation of the aluminum alloy sheet belt material.
[0029] In another typical embodiment of the present application, a method for manufacturing the aluminum alloy sheet belt material is provided, the manufacturing method comprising the steps of casting, heat treatment, hot rolling, primary cold rolling, intermediate annealing, and secondary cold rolling, which are performed sequentially, wherein the temperature of the intermediate annealing step is 420 to 440°C and the cooling water temperature of the casting step is 19 to 25°C.
[0030] An aluminum alloy liquid containing Si, Fe, Cu, Mn, Mg, Zn, and Ti elements is formed by smelting, and this aluminum alloy liquid is then cast to form an aluminum alloy. One of the surface defects in the untreated printing plate base is streak defects. Streak defects mainly appear in the central region of the aluminum alloy sheet belt material, exhibiting a strip-like distribution along the rolling direction, and are numerous and large in area (width 1-5 mm, length 10-100 m), severely affecting printing quality. By comparing and examining the metallic properties of normal and defective regions, researchers discovered that the larger the size of the Fe-containing phase in the streak defect region (approximately 10 μm), and the larger the size of the Fe-containing second phase, the larger the pit defects, and the more Fe-containing second phases there are, the more pit defects there are. The reason for this is that in the aluminum alloy casting process, the high-melting-point Fe-containing phase segregates due to uneven cooling, forming a segregation distribution along the rolling direction. This invention helps to refine the Fe-containing phase crystal particles and improve the uniformity of the Fe-containing phase crystal particle distribution by controlling the temperature of the cooling water during casting within the above range. Consequently, the number density of the Fe-containing second phase in aluminum alloy plate belt material exceeding a length of 5 μm is ≤10 particles / mm². 2 Furthermore, this improves the surface quality of the aluminum alloy sheet belt material. Heat treatment of the aluminum alloy contributes to making the internal structure of the aluminum alloy sheet belt material more uniform, thereby improving the strength and plasticity of the aluminum alloy sheet belt material. Hot rolling of the aluminum alloy after heat treatment contributes to further improving the strength and plasticity of the aluminum alloy sheet belt material. Performing primary cold rolling on the aluminum alloy after hot rolling is advantageous in improving the surface cleanliness and flatness of the aluminum alloy sheet belt material. Intermediate annealing is performed on the aluminum alloy after primary cold rolling, and preferably, by controlling the temperature of the intermediate annealing to the above range, it is possible to refine the size of the crystal grains, randomize the orientation, improve the uniformity of the dispersion of the crystal grains, and promote the solid solution of the Mg-Si phase, and therefore it is advantageous in forming a multilayer sandy texture on the surface of the aluminum alloy sheet belt material after electrolytic corrosion. Secondary cold rolling is performed on the aluminum alloy after annealing to form the aluminum alloy sheet belt material, and finally, an aluminum alloy sheet belt material with excellent overall properties is obtained.
[0031] Furthermore, the above intermediate annealing process shows the relationship between crystal grain size and the influence of Mg-Si on the grain texture of aluminum alloy plate belt material for printing plate bases that do not require further processing.
[0032] Preferably, the casting process of this application is divided into two steps: smelting and semi-continuous casting.
[0033] In order to further refine the crystal grain size, in one embodiment of the present invention, preferably, in the intermediate annealing step, the heating rate is 20 to 30°C / hour and the holding time is 2 to 4 hours.
[0034] To further improve the uniformity of the internal structure of the aluminum alloy plate belt material, in one embodiment of the present invention, the resting time after the casting process is preferably 30 to 50 minutes, and / or the temperature of the heat treatment process is 440 to 480°C.
[0035] In one embodiment of the present invention, the starting temperature for the hot rolling process is 420 to 460°C, and / or the final rolling temperature is 270 to 310°C.
[0036] If the hot rolling temperature is too high or too low, it is detrimental to improving the strength and plasticity of the aluminum alloy sheet belt material. Preferably, controlling the starting temperature and final rolling temperature of the hot rolling process within the above range contributes to improving the resistance to softening deformation of the aluminum alloy sheet belt material.
[0037] In one embodiment of the present invention, the rolling speed in the primary cold rolling process is 300 to 1000 m / min.
[0038] If the rolling speed is too fast, it is detrimental to the formation of regular crystal grains, and if the rolling speed is too slow, it is detrimental to the refinement of crystal grains. Therefore, preferably, controlling the rolling speed of the primary cold rolling within the above range contributes to improving the strength of the aluminum alloy sheet belt material.
[0039] To improve the uniformity of the thickness of the aluminum alloy sheet belt material and to rationally control the surface roughness of the aluminum alloy sheet belt material, in one embodiment of the present invention, preferably, the surface roughness of the rolling roller in the secondary cold rolling process is 0.3 to 0.4 μm, and / or the cold rolling rate in the secondary cold rolling process is 80 to 90%, which helps to improve the effect of secondary cold rolling.
[0040] The beneficial effects of this application will be further explained below with reference to the examples.
[0041] (Example 1) The composition of the aluminum alloy plate belt material for the no-process printing plate base is as follows, by mass percentage: Si content 0.03%, Fe content 0.31%, Cu content 0.01%, Mn content 0.01%, Mg content 0.19%, Zn content 0.01%, Ti content 0.01%, with the remainder being Al and several types of unavoidable impurities, where each type of impurity is less than 0.05%, and the total impurity content is less than 0.15%.
[0042] The manufacturing process includes the following steps:
[0043] In the casting process of S1, flat ingots of aluminum alloy are produced using smelting and semi-continuous casting methods. The smelting and resting time is 30 minutes, and the cooling water temperature for semi-continuous casting is 22°C. In the heating process of S2, the heating temperature of the aluminum alloy ingot is 440°C. In the hot rolling process of S3, the rolling start temperature is 420°C and the final rolling temperature is 270°C. In the primary cold rolling process of S4, the rolling speed is 1000 m / min. In the intermediate annealing process of S5, the annealing temperature is 420°C, the heating rate is 20°C / hour, and the holding time is 2 hours. In the S6 secondary cold rolling process, the cold rolling rate is 80%, the surface roughness of the rolling rollers is 0.3 μm, and the thickness of the rolled aluminum alloy sheet belt is 0.23 mm.
[0044] The area proportion of deformed crystalline particles in the manufactured aluminum alloy plate belt material was 94%, and the number density of Fe-containing second phase particles exceeding 5 μm in length was 10 particles / mm². 2 The maximum diameter of the pits on the anodized surface is 0.12 mm. In the aluminum alloy plate belt material for the printing plate base that does not require processing, the precipitation and redissolution of the Mg2Si phase before and after intermediate annealing is shown in Figure 1, the distribution of the Fe-containing second phase is shown in Figure 2, the area ratio diagram of deformed crystal grains is shown in Figure 3, the distribution diagram of surface roughness before and after sanding is shown in Figure 4, and the three-dimensional shape of the surface after anodizing is shown in Figure 5.
[0045] (Example 2) The differences from Example 1 are as follows: The alloy composition of the aluminum alloy sheet belt material is as follows: Si content 0.08%, Fe content 0.25%, Cu content 0.01%, Mn content 0.01%, Mg content 0.26%, Zn content 0.01%, and Ti content 0.01%. Finally, an aluminum alloy sheet belt material was obtained, and the area ratio occupied by deformed crystal grains in the manufactured aluminum alloy sheet belt material was 91%, and the number density of Fe-containing second phase exceeding 5 μm in length was 4 grains / mm². 2 The maximum diameter of the pits on the anodized surface is 0.07 mm.
[0046] (Example 3) The differences from Example 1 are as follows: The alloy composition of the aluminum alloy sheet belt material is as follows: Si content 0.08%, Fe content 0.12%, Cu content 0.01%, Mn content 0.01%, Mg content 0.32%, Zn content 0.01%, and Ti content 0.01%. Finally, an aluminum alloy sheet belt material was obtained, and the area ratio occupied by deformed crystal grains in the manufactured aluminum alloy sheet belt material was 95%, and the number density of Fe-containing second phase exceeding 5 μm in length was 1 grain / mm². 2 The maximum diameter of the pits on the anodized surface is 0.06 mm.
[0047] (Example 4) The differences from Example 1 are as follows. The temperature rising rate of intermediate annealing is 30°C / hour, finally, an aluminum alloy sheet belt material is obtained, and the number density of Fe-containing second phases with a length exceeding 5 μm in the aluminum alloy sheet belt material is 1 piece / mm 2 , the proportion of deformed crystal grains in the aluminum alloy sheet belt material is 96%, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.05 mm.
[0048] (Example 5) The differences from Example 1 are as follows. The temperature of the heat treatment is 480°C, finally, an aluminum alloy sheet belt material is obtained, and the number density of Fe-containing second phases with a length exceeding 5 μm in the aluminum alloy sheet belt material is 2 pieces / mm 2 , the proportion of deformed crystal grains in the aluminum alloy sheet belt material is 92%, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.09 mm.
[0049] (Example 6) The differences from Example 1 are as follows. The rolling start temperature of the hot rolling step is 460°C, the final rolling temperature is 310°C, finally, an aluminum alloy sheet belt material is obtained, and the number density of Fe-containing second phases with a length exceeding 5 μm in the aluminum alloy sheet belt material is 2 pieces / mm 2 , the proportion of deformed crystal grains in the aluminum alloy sheet belt material is 91%, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.11 mm.
[0050] (Example 7) The differences from Example 1 are as follows. The rolling speed in the primary cold rolling step is 300 m / min, finally, an aluminum alloy sheet belt material is obtained, and the number density of Fe-containing second phases with a length exceeding 5 μm in the aluminum alloy sheet belt material is 3 pieces / mm 2 , the proportion of deformed crystal grains in the aluminum alloy sheet belt material is 91%, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.14 mm.
[0051] (Example 8) The differences from Example 1 are as follows: The surface roughness of the rolling roller in the secondary cold rolling process was 0.4 μm, and finally, an aluminum alloy sheet belt was obtained, with a number density of Fe-containing second phases exceeding 5 μm in length of 1 particle / mm² in the aluminum alloy sheet belt. 2 The proportion of deformed crystal grains in the aluminum alloy sheet belt material is 93%, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.12 mm.
[0052] (Example 9) The differences from Example 1 are as follows: The cold rolling rate in the secondary cold rolling process was 90%, and finally, an aluminum alloy sheet belt was obtained, with a number density of Fe-containing second phases exceeding 5 μm in length of 7 particles / mm² in the aluminum alloy sheet belt. 2 The proportion of deformed crystalline grains in the aluminum alloy sheet belt material is 98% by weight, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.13 mm.
[0053] (Comparative Example 1) The difference from Example 1 is that intermediate annealing is not performed in the manufacturing process. The area ratio of deformed crystal grains in the manufactured aluminum alloy sheet belt material is 81%, and the number density of Fe-containing second phases exceeding 5 μm in length in the aluminum alloy sheet belt material is 6 particles / mm². 2 The diameter of the pit defects on the anodized surface of the aluminum alloy plate belt material is 0.41 mm. Figure 6 shows the area ratio of deformed crystal particles in the aluminum alloy plate belt material for the no-treatment printing plate base (light colors represent deformed crystal particles, dark colors represent recrystallized particles), and Figure 7 shows the distribution of surface roughness of the aluminum alloy plate belt material for the no-treatment printing plate base before and after sandblasting.
[0054] (Comparative Example 2) The difference from Example 1 is that the temperature of the semi-continuous casting cooling water in the manufacturing process is 28°C ± 3°C. The number density of Fe-containing second phases exceeding 5 μm in length in the manufactured aluminum alloy plate belt material is 20 particles / mm². 2 The proportion of deformed crystal grains in the aluminum alloy plate belt material is 88%, the diameter of the pit defects on the anodized surface is 0.52 mm, the distribution map of the Fe-containing second phase of the aluminum alloy plate belt material for the no-treatment printing plate base and a partially enlarged view thereof are shown in Figure 8, and the three-dimensional profile of the surface of the aluminum alloy plate belt material for the no-treatment printing plate base after anodizing is shown in Figure 9.
[0055] (Comparative Example 3) The differences from Example 1 are as follows: In terms of mass percentage, the composition is as follows: Si content 0.08%, Fe content 0.37%, Cu content 0.05%, Mn content 0.01%, Mg content 0%, Zn content 0.01%, and Ti content 0.01%. Finally, an aluminum alloy sheet belt material was obtained, and the number density of Fe-containing second phases exceeding 5 μm in length in the aluminum alloy sheet belt material was 15 particles / mm². 2 The proportion of deformed crystal grains in the aluminum alloy sheet belt material is 86%, and the diameter of pit defects on the anodized surface of the aluminum alloy sheet belt material is 0.34 mm.
[0056] (Comparative Example 4) The differences from Example 1 are as follows: The Si content is 0.15%, the Fe content is 0.4%, the Cu content is 0.1%, and the Mg content is 0.1%. Finally, an aluminum alloy plate belt material was obtained, and the number density of the Fe-containing second phase exceeding 5 μm in length in the aluminum alloy plate belt material was 27 particles / mm². 2 The proportion of deformed crystal grains in the aluminum alloy sheet belt material is 79%, and the diameter of the pit defects on the anodized surface of the aluminum alloy sheet belt material is 55 mm.
[0057] The aluminum alloy plate belt materials produced in the above examples and comparative examples were tested for tensile strength, yield strength, elongation, electrode potential, roughness, electrolytic sand roughness, color difference ΔE, and brightness difference ΔL, and the results are shown in Table 1.
[0058] [Table 1]
[0059] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects.
[0060] The present invention improves the synergistic effect of each element by controlling the content of each element within the above range, and compared to the prior art, the present invention reduces the content of Cu, Si, and Fe and increases the content of Mg, thereby giving the manufactured aluminum alloy plate belt material for no-process printing plate bases the above-mentioned tensile strength, electrolytic sand roughness, electrode potential, and surface quality (specifically, by controlling the number density and size of the Fe-containing second phase in the present invention within the above range, it contributes to reducing the degree of streak defects on the surface of the aluminum alloy plate belt material. The above-mentioned low electrode potential helps to form a multilayer sand texture on the surface of the aluminum alloy plate belt material after electrolytic treatment). Furthermore, this gives the aluminum alloy plate belt material for no-process printing plate bases high resistance to softening deformation, high resolution, and print resistance, thus solving the problem of difficulty in matching the tensile strength and sand texture performance of the aluminum alloy plate belt material for no-process printing plate bases.
[0061] The above description is merely an embodiment of the present invention and is not intended to limit the invention, and various modifications and changes can be made to those skilled in the art. Any modifications, equivalent replacements, improvements, etc., made within the spirit and principles of the invention should be included within the scope of protection of the invention.
Claims
1. An aluminum alloy plate belt material for a no-process printing plate base, wherein, by mass percentage, the aluminum alloy plate belt material contains 0.02% to 0.10% Si, 0.10% to 0.35% Fe, <0.05% Cu, <0.02% Mn, 0.17% to 0.35% Mg, <0.02% Zn, and <0.03% Ti, with the remainder being Al and several types of unavoidable impurities, the total impurity content being <0.15%, and the content of any single impurity being <0.05%. However, the tensile strength of the aluminum alloy plate belt material is 170 MPa to 210 MPa. The electrolytic sand roughness Ra of the aluminum alloy plate belt material is 0.45 μm to 0.55 μm, and Rz is 3.50 μm to 4.60 μm. The electrode potential of the aluminum alloy plate belt material is -0.7V to -0.9V. The number density of Fe-containing second phases exceeding 5 μm in length in the aforementioned aluminum alloy plate belt material is ≤10 particles / mm². 2 The aluminum alloy plate belt material is characterized in that the area ratio occupied by deformed crystal particles in the aluminum alloy plate belt material is ≥ 90%.
2. The aluminum alloy plate belt material according to claim 1, characterized in that the roughness Ra of the aluminum alloy plate belt material is 0.2 μm to 0.3 μm and the Rz is 1.5 μm to 2.5 μm.
3. The aluminum alloy plate belt material according to claim 1 or 2, characterized in that, after anodizing, the diameter of pit defects on the anodized surface of the aluminum alloy plate belt material is <0.2 mm, and / or the color difference ΔE on the anodized surface of the aluminum alloy plate belt material is <0.25, and / or the brightness difference ΔL on the anodized surface of the aluminum alloy plate belt material is <0.
25.
4. The aluminum alloy plate belt material according to claim 1 or 2, characterized in that the yield strength of the aluminum alloy plate belt material is ≥ 160 MPa and / or the elongation of the aluminum alloy plate belt material is ≥ 1%.
5. The manufacturing method includes a process of sequentially performing casting, heat treatment, hot rolling, primary cold rolling, intermediate annealing, and secondary cold rolling. The method for manufacturing an aluminum alloy plate belt material according to claim 1 or 2, characterized in that the temperature of the intermediate annealing process is 420°C to 440°C, and the cooling water temperature of the casting process is 19°C to 25°C.
6. The manufacturing method according to claim 5, characterized in that in the intermediate annealing step, the heating rate is 20°C / hour to 30°C / hour and the holding time is 2 hours to 4 hours.
7. The manufacturing method according to claim 5, characterized in that the settling time after the casting process is 30 to 50 minutes, and / or the temperature of the heat treatment process is 440°C to 480°C.
8. The manufacturing method according to claim 5, characterized in that the rolling start temperature of the hot rolling process is 420°C to 460°C, and / or the final rolling temperature is 270°C to 310°C.
9. The manufacturing method according to claim 5, characterized in that the rolling speed in the primary cold rolling process is 300 m / min to 1000 m / min.
10. The manufacturing method according to claim 5, characterized in that the surface roughness of the rolling roller in the secondary cold rolling step is 0.3 μm to 0.4 μm, and / or the cold rolling rate in the secondary cold rolling step is 80% to 90%.
Citation Information
Patent Citations
Method for producing substrate of precoated sensitive plate from aluminum alloy
CN101338393A
Supporter for lithographic printing plate and its manufacture
JP1986146598A
Lithographic printing plate having smooth and lustrous surface
JP1997226263A
Manufacture of aluminum alloy support for lithographic printing plate and aluminum alloy support for lithographic printing plate
JP1999061364A
Aluminum support for lithographic printing plate and method for roughing it
JP1999286183A